Intestinal current measurement detects age-dependent differences in CFTR function in rectal epithelium - Graeber, Simon Y.; Sommerburg, Olaf; Yu, Yin; Berges, Julian; Hirtz, Stephanie; Scheuermann, Heike; Berger, Jasmin; Duerr, Julia; Mall, Marcus A. (Frontiers in Pharmacology, 2025)
ObjectiveIntestinal current measurement (ICM) provides a sensitive bioassay for assessment of cystic fibrosis transmembrane conductance regulator (CFTR) function in rectal biopsies ex vivo and is used as a diagnostic tool for cystic fibrosis (CF). Furthermore, ICM was shown to be sensitive to detect pharmacological rescue of CFTR function by CFTR modulators in people with CF carrying responsive CFTR mutations. Results from clinical trials of CFTR modulators across age groups indicate that CFTR function in the sweat duct may be age-dependent with children reaching higher levels than adults. However, little is known about age dependency of CFTR function in the intestinal epithelium.MethodsWe investigated CFTR-mediated chloride secretion in rectal biopsies from 258 people without CF and 72 people with pancreatic-insufficient CF from 1 month to 68 years of age. Change in transepithelial short-circuit current in response to cyclic adenosine monophosphate (cAMP)-mediated (100 μM IBMX, 1 µM forskolin, basolateral) and cholinergic (100 μM carbachol, basolateral) stimulation was assessed as a readout for CFTR function using perfused micro-Ussing chambers. Furthermore, quantitative real-time PCR of CFTR and morphometric analysis of epithelial cells lining the crypts and surface of the rectal mucosa were performed to assess regulation at the levels of gene expression and epithelial cell densities.ResultsWe found that CFTR-mediated chloride secretion across rectal tissues, as determined from cAMP-mediated as well as cholinergic chloride-secretory responses was highest during infancy and early childhood and declined with age in people without CF (both P < 0.001). Although, there was no difference in cAMP-mediated currents in people with CF, potassium-secretory responses induced by cholinergic stimulation were also reduced with increasing age. Transcript analyses showed that CFTR mRNA expression was slightly increased with increasing age in people without CF (P < 0.05). Morphometric analyses demonstrated that CFTR expressing colonocytes at the crypt base were decreased with age (P < 0.05). A secondary analysis of the ICM data of our previous studies on the effects of lumacaftor/ivacaftor on CFTR function in F508del -homozygous people with CF aged 12 years and older and 2–11 year old children showed correlations of the change in cAMP-mediated and cholinergic chloride secretory response with the age of people with CF (P < 0.01 and P < 0.05, respectively).ConclusionThese results demonstrate that CFTR function in the rectal epithelium is reduced with increasing age and indicate that this change is likely due to a decline in the number of secretory colonocytes at the crypt base. These findings suggest that differences in CFTR expressing cells may explain increased functional responses to CFTR modulator therapies in children compared to adult people with CF.